Pelatihan Clinical Instructure (Ci) RSI PKU Muhammadiyah Tegal - Arif Rakhman; Ratna Widhiastuti; Deni Irawan (UNIVERSITAS BHAMADA SLAWI, 2020)
The function of the hospital as a place to organize medical services, administration, and management, medical support, can also be empowered to place education and training, development and quality control of nursing through the development of nursing practice land accompanied by the development of nursing professional community to gain experience in learning in the field correctly for students (MOH RI, 2006). In this case, a clinical instrument is a very necessary means to carry out professional attitudes and skills for nurses. One of the absolute means is the existence of nurses who are professional as clinical instructors who will guide students so that professional development can develop for nurses in the future. However, there is one problem which is the availability of competent human resources or nurses. This includes many clinical instructors with diploma education and minimal experience in guiding. The aim of community service is that clinical instruction (CI) can carry out the process of mentoring and mentoring to students practicing in hospitals so that the expected learning objectives can be achieved. The target activity is nurses PKU Muhammadiyah Hospital, amounting to 30 people. The results of this activity are during the process of participant listening, discussion and being able to practice clinical infrastructure in the room so that the expected learning objectives can be achieved.